Discourses around the digital and academic literacy: towards an integrative model - López-Andrada, Concepción (Universidad Nacional de Córdoba, Faculdad de Ciencias Sociales, Centro de Estudios Avanzados. Maestría en Procesos Educativos Mediados por Tecnología, 2016)
The purpose of this brief analysis focuses on the presentation of some current trends on reading and academic practices mediated by technologies. This analysis starts from the discursive point of view, since it focuses on the articulation of a series of narrations ranging from the uncritical view of technology to the integration of interdisciplinary and inclusive elements that some authors have presented as inescapable dynamics in the accomplishment of academic spaces. The Information and Communications Technologies face the literate person to new types of texts, multiple types of reading and writing practices, and new ways to receive, understand and interpret the information. These aspects would include new definitions of literacy that can be synthesized in the ability of an individual to interact with any culturally coded symbolic system.